`h(x) = 6x^-2 + 7x^2` Find the second derivative of the function.

Textbook Question

Chapter 2, Review - Problem 46 - Calculus of a Single Variable (10th Edition, Ron Larson).
See all solutions for this textbook.

1 Answer | Add Yours

hkj1385's profile pic

hkj1385 | (Level 1) Assistant Educator

Posted on

Note:- If y = x^n ; where n = constant ; then dy/dx = n*x^(n-1)

Now,

`h(x) = 6x^-2 + 7x^2`

`h'(x) = -12x^-3 + 14x`

`h''(x) = -12*(-3)*x^-4 + 14`

`or, h''(x) = 36x^-4 + 14`

``

We’ve answered 318,960 questions. We can answer yours, too.

Ask a question